White teeth : a novel - Smith, Zadie (September 2004., 2001)
On New Year's morning, 1975, Archie Jones sits in his car on a London road and waits for the exhaust fumes to fill his Cavalier Musketeer station wagon. Archie--working-class, ordinary, a failed marriage under his belt--is calling it quits, the deciding factor being the flip of a 20-pence coin. When the owner of a nearby halal butcher shop (annoyed that Archie's car is blocking his delivery area) comes out and bangs on the window, he gives Archie another chance at life and sets in motion this richly imagined, uproariously funny novel. Set in post-war London, this novel of the racial, political, and social upheaval of the last half-century follows two families--the Joneses and the Iqbals, both outsiders from within the former British empire--as they make their way in modern England.